PENGETAHUAN DAN KETERAMPILAN BIDAN DESA DALAM PELAYANAN ANTENATAL CARE - Zuhaeri, Muhamad (MEDIA ILMU KESEHATAN, 2019)
Background: Various context and structure conditions in health care system will be affected the effectiveness of maternal and child health programs particularly antenatal care. More efforts have been done to improve those programs such as increasing knowledge and skills that have supported by the organization. Education and training programs is one of programs that were shown to improve the mastery of midwifery care competencies related to mastery of services standard based antenatal care competencies. Objectives: The purposes of this study were to evaluate the quality of clinical assessment knowledge and clinical assessment skills for the village midwives in antenatal care. Methods: The design of this study was kuantitative methods approaches with cross sectional study. Results: Analysis indicated that 23.6% univariabel village midwives didn’t know about clinical asesmentin antenatal care, 61.8% did village midwives in the practice of clinical asesment antenatal care, andvillage midwives 49.1% had no antenatal care is a complete equipment. Bivariabel analysis showed asignificant association between clinical knowledge with clinical asesment asesment in practice antenatal care (p <0.05). Conclusion: The relationship of clinical knowledge to the practice Clinical asesment asesment in antenatal care indicated a significant relationship (p = <0.05). Keywords: Clinical assessment, antenatal care